Acrylate emulsion resistant to high temperature and low temperature as well as preparation method and application of acrylate emulsion

By using semi-continuous seed emulsion polymerization and modification with vinyl silicone oil and epoxy resin, the problems of adhesion at high temperatures and brittleness at low temperatures of acrylate emulsions have been solved, thereby improving their high and low temperature resistance and making them suitable for textile coating finishing agents.

CN121293439APending Publication Date: 2026-01-09ZHEJIANG SCI-TECH UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511616844.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-06
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Traditional acrylic emulsions tend to become sticky at high temperatures and brittle at low temperatures, limiting their application in extreme temperature environments, especially exhibiting adhesion and cracking problems in textile processing and low-temperature outdoor environments.

Method used

A semi-continuous seed emulsion polymerization method was adopted, which introduced vinyl silicone oil and epoxy resin modified acrylate emulsion to improve the high and low temperature resistance of the coating by forming a three-dimensional network structure and reducing surface free energy.

Benefits of technology

This achievement enables acrylic emulsions to remain non-sticky at 50°C and non-brittle at -30°C, expanding their application range and improving the overall performance and stability of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121293439A_ABST
    Figure CN121293439A_ABST
Patent Text Reader

Abstract

The invention discloses a high and low temperature resistant acrylate emulsion, a preparation method thereof and application of the acrylate emulsion as a high and low temperature resistant film-forming agent in a fabric coating finishing agent. The acrylate emulsion is prepared from the following raw materials in percentage by mass: 30%-35% of butyl acrylate, 3%-6% of styrene, 1%-2% of acrylic acid, 5%-10% of acrylonitrile, 5%-10% of 2-ethylhexyl acrylate, 4%-6% of epoxy resin E51, 1.9%-2.1% of vinyl silicone oil, 0.5%-1% of sodium bicarbonate, 2.2%-2.4% of 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate, 0.14%-0.16% of succinic acid alkyl ester sodium disulfonate, 0.37%-0.39% of ammonium persulfate and the balance of water. The theoretical glass transition temperature of the acrylate emulsion is-35 to-40 DEG C. The preparation method adopts semi-continuous seed emulsion polymerization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of waterborne acrylic emulsions, specifically to a high and low temperature resistant acrylic emulsion, its preparation method, and its application. Background Technology

[0002] Acrylic ester emulsions are an important polymer material, widely used in textile finishing, coatings and adhesives due to their excellent film-forming properties, weather resistance and environmental protection characteristics.

[0003] Acrylic emulsions, as important film-forming materials, occupy a pivotal position in the coating and finishing field. With their excellent film-forming properties, weather resistance, and moderate cost, they are widely used in various industries such as textiles, leather, and coatings. In the textile industry, acrylic emulsions are often used for coating and finishing fabrics, imparting properties such as a soft hand feel and wrinkle resistance. In the leather industry, they can improve the abrasion resistance and water resistance of leather. In the coatings field, they can effectively improve the gloss and adhesion of coatings.

[0004] Acrylic emulsions have excellent film-forming properties, weather resistance, and adhesion, and are widely used in textile finishing, adhesives, coatings and other fields. However, acrylic emulsions also exhibit the disadvantages of being hot-sticky and cold-brittle. They tend to become sticky at high temperatures and brittle at low temperatures, which greatly affects the application of acrylic emulsions in some extreme conditions.

[0005] Acrylic emulsions exhibit significant performance limitations when exposed to extreme temperature conditions. At high temperatures, acrylic emulsion coatings are prone to adhesion, which not only damages the product's appearance but also hinders subsequent processing and use. For instance, during high-temperature drying or storage, adhesion between coating layers reduces product quality and production efficiency. Conversely, at low temperatures, acrylic emulsion coatings become brittle and lack flexibility, making them highly susceptible to cracking and peeling under external forces. This severely impacts product lifespan, particularly pronounced in outdoor applications in cold regions.

[0006] Traditional acrylic emulsions are prone to becoming sticky at high temperatures and brittle at low temperatures under extreme conditions, severely limiting their applicability in textile processing. For example, at high temperatures, emulsion-coated fabrics may stick to the rollers, affecting production efficiency; at low temperatures, the coating is prone to embrittlement and cracking, reducing the fabric's lifespan. Therefore, developing an acrylic emulsion that combines high-temperature anti-sticking and low-temperature anti-brittleness properties has become an important research direction in the field of textile chemicals.

[0007] In recent years, researchers have optimized the properties of acrylic emulsions through modification techniques, mainly focusing on the following areas: Crosslinking technology: Introducing room temperature self-crosslinking systems (such as metal ions, siloxane groups, or carbonyl-hydrazide systems) enhances the mechanical stability of the coating by forming a three-dimensional network structure, thereby improving the low-temperature brittleness problem.

[0008] Nanomaterial composites: For example, adding nanocellulose can significantly reduce the adhesion of emulsions, solve the problem of sticking to rollers in high-temperature processing, and at the same time improve the dispersion stability of emulsions.

[0009] Copolymer design: By copolymerizing polyurethane and acrylate, a balance of temperature adaptability is achieved by combining the elasticity of polyurethane with the rigidity of acrylate.

[0010] Despite some progress in existing research, synergistically optimizing high-temperature and low-temperature performance remains a technical challenge. For example, excessive crosslinking agents may lead to overly hard coatings, while insufficient dispersibility of nanomaterials can easily cause aggregation effects. Furthermore, existing modification methods mostly focus on improving a single property, lacking comprehensive consideration of complex working conditions in textile processing (such as dynamic temperature changes and mechanical stress).

[0011] From the perspective of the current development of the textile industry, developing acrylic emulsions with high-temperature anti-sticking and low-temperature anti-brittleness properties is of paramount practical significance. In the textile printing and dyeing industry, high-temperature drying and heat setting are common processing steps. However, traditional acrylic emulsions are prone to sticking to equipment during these high-temperature processes. This not only reduces production efficiency and increases production costs but also affects product quality, resulting in defective and waste products. Simultaneously, in cold outdoor wear and some low-temperature industrial environments, the coating on the fabric surface is prone to becoming brittle, significantly reducing the fabric's flexibility and durability, failing to meet the needs of consumers and industrial users. Summary of the Invention

[0012] To address the aforementioned technical problems and shortcomings in the field, this invention provides a high and low temperature resistant acrylate emulsion, its preparation method, and its application.

[0013] The specific technical solution is as follows: In a first aspect, the present invention provides a method for preparing a high- and low-temperature resistant acrylate emulsion, wherein the raw material composition of the high- and low-temperature resistant acrylate emulsion, by mass fraction, is: 30%~35% (e.g., 31%, 32%, 33%, 34%, etc.) butyl acrylate (BA), 3%~6% (e.g., 4%, 5%, etc.) styrene (ST), 1%~2% (e.g., 1.5%, etc.) acrylic acid (AA), 5%~10% (e.g., 6%, 7%, 8%, 9%, etc.) acrylonitrile (AN), and 5%~10% (e.g., 6%, 7%, 8%, 9%, etc.) isoacrylate. Octyl ester (2-EHA), 4%~6% preferably 5% epoxy resin E51, 1.9%~2.1% preferably 2% vinyl silicone oil, 0.5%~1% sodium bicarbonate, 2.2%~2.4% preferably 2.3% emulsifier 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate (CAS No.: 184719-88-8), 0.14%~0.16% preferably 0.15% adhesive alkyl succinate disulfonate sodium and 0.37%~0.39% preferably 0.38% ammonium persulfate (APS), and the balance being water; The theoretical glass transition temperature of the high and low temperature resistant acrylic emulsion, calculated using the Fox equation, is -35 to -40°C. The preparation method employs a semi-continuous seed emulsion polymerization method, specifically including the following steps: (1) Epoxy resin E51, vinyl silicone oil, water, sodium bicarbonate and emulsifier 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate are mixed and then mixed monomers are added. The mixed monomers are butyl acrylate, styrene, acrylic acid, acrylonitrile and isooctyl acrylate. The mixture is stirred to form a pre-emulsion. (2) Take a portion of the pre-emulsion and mix it with water and the adhesive sodium alkyl succinate disulfonate. Heat it to 80-82°C in an inert atmosphere under stirring at 250-300 rpm, preferably 275 rpm. Then add a portion of ammonium persulfate aqueous solution and keep it warm for 15-20 minutes to obtain the seed emulsion. Then add the remaining pre-emulsion dropwise to the seed emulsion. After the addition is complete, keep it warm for 3-4 hours. Then add the remaining ammonium persulfate aqueous solution and continue to keep it warm for 1-1.5 hours. Cool down and adjust the pH to >7. Filter to obtain the high and low temperature resistant acrylate emulsion.

[0014] This invention modifies acrylate emulsions. Vinyl silicone oil has a unique molecular structure, with its main chain composed of silicon-oxygen bonds and side chains containing vinyl groups, giving it excellent high and low temperature resistance, low surface energy, and good flexibility. Introducing vinyl silicone oil into the acrylate emulsion system can reduce the surface free energy of the coating, thereby effectively preventing adhesion at high temperatures, while enhancing the flexibility of the coating at low temperatures and reducing the risk of brittleness. Epoxy resin, with its highly cross-linked three-dimensional network structure, endows the material with high strength, high adhesion, and excellent chemical stability. After being compounded with acrylate emulsions, epoxy resin can enhance the mechanical properties of the coating, improve the adhesion between the coating and the substrate, and further optimize the overall performance of the coating under different temperature conditions.

[0015] Modifying acrylate emulsions with vinyl silicone oil and epoxy resin to achieve high-temperature non-stickiness and low-temperature non-brittleness is of great practical significance for expanding the application range of acrylate emulsions and improving the performance and quality of related products.

[0016] This invention employs a semi-continuous seed emulsion polymerization method, following the reaction mechanism of free radical polymerization. Ammonium persulfate is used as the initiator. Upon heating, the initiator decomposes to generate free radicals, which first undergo addition reactions with monomer molecules to form monomer free radicals. These monomer free radicals are highly reactive and rapidly undergo chain reactions with other monomer molecules, continuously adding new monomer molecules and causing the polymer chain to grow rapidly. During this growth process, due to the presence of numerous micelles formed by monomers and emulsifiers in the system, polymer chain growth mainly occurs within the micelles or on the surface of monomer droplets. The polymerization reaction terminates when the monomer concentration in the system decreases to a certain level or when interactions occur between polymer chains.

[0017] In this invention, an inert atmosphere refers to a gaseous atmosphere that does not participate in the reaction, such as a nitrogen (N2) atmosphere.

[0018] The Fox equation is a well-known existing technology. The calculation process for the theoretical glass transition temperature is as follows: The composition of each monomer can be determined by the raw material composition, and the mass fraction (w) of each monomer can be obtained by calculation. i (where i is the monomer label), find the glass transition temperature of each monomer and denote it as Tg,i. The theoretical glass transition temperature (Tg) of the acrylate emulsion can be calculated using the Fox equation: Where n represents the total number of individuals.

[0019] According to the Fox equation, the high and low temperature resistant acrylate emulsion can be made to have the desired theoretical glass transition temperature by adjusting the amount and ratio of each monomer.

[0020] In the preparation method of the high and low temperature resistant acrylate emulsion described in the first aspect, in step (2), if the experimental reaction temperature is too high, the molecular activity increases, the molecular motion of the reactants intensifies, and the frequency and number of molecular collisions increase. On the other hand, the decomposition rate of the initiator increases, the number of free radical groups generated increases, and the reaction becomes more intense, which may cause the reaction gel rate to be too high, or even cause dangerous situations such as reaction burst polymerization, thus leading to reaction failure. If the reaction temperature is too low, the initiator activity is insufficient, and fewer free radical groups are generated, ultimately leading to incomplete monomer reaction and low monomer conversion rate. If the reaction temperature is too high or too low, the emulsification effect of the emulsifier will be worse, which is also not conducive to the stability of the emulsion. The present invention found that when the reaction temperature is low, the monomer conversion rate of the reaction is low, and when the reaction temperature is too high, the gel rate of the emulsion is high. Considering all factors, 80~82℃ was finally determined to be the most suitable temperature for the experimental reaction.

[0021] In the method for preparing the high and low temperature resistant acrylate emulsion described in the first aspect, in step (2), the stirring rate has a significant impact on the reaction during emulsion polymerization. From a microscopic perspective, stirring can increase the collision probability of each reactant molecule. When the stirring rate is appropriate, the monomer, initiator, and emulsifier can be fully mixed. The free radicals generated by the decomposition of the initiator can quickly contact the monomer, accelerate the chain initiation and chain growth reactions, and increase the polymerization rate. Moreover, appropriate stirring is conducive to the formation of monomer droplets of uniform size, and the latex particles with uniform particle size are obtained through polymerization, which enhances the stability of the emulsion. However, if the stirring rate is too high, it will destroy the emulsifier film on the surface of the latex particles, leading to the aggregation of latex particles, and will also accelerate the free radical termination reaction, reducing the molecular weight of the polymer. This invention found that at a rotation speed of 200 rpm, both heat and mass transfer deteriorate, causing latex particles to aggregate and resulting in increased gelation, while the monomer conversion rate is also relatively low. When the rotation speed reaches 350 rpm, the emulsifier film on the surface of the latex particles is easily damaged, causing the latex particles to aggregate and form gel. Excessive rotation speed can also accelerate the free radical termination reaction and reduce the monomer conversion rate. In summary, the reaction rate should be controlled between 250 and 300 rpm, with the lowest gelation rate at a rotation speed of 275 rpm.

[0022] In emulsion polymerization, emulsifiers are an indispensable component. Emulsifiers have hydrophilic and hydrophobic ends. The hydrophilic end interacts with water molecules, while the hydrophobic end interacts with monomer molecules. Therefore, emulsifiers can oriented between monomers and water molecules, thereby reducing surface tension. Emulsifier molecules form a dense emulsion film on the monomer surface. This emulsion film can reduce collisions and friction between particles, thus maintaining system stability. This invention found that when the amount of 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate added is 1.7% of the mass of the acrylate emulsion raw material, the emulsion separates after 72 hours. The latex film on the particle surface is not perfectly formed, the interfacial tension is not sufficiently reduced, and the electrostatic repulsion and steric hindrance are weakened, leading to emulsion instability. The monomer conversion rate of the emulsion initially increases and then decreases with increasing emulsifier dosage. Low emulsifier dosage results in fewer micelles and fewer nucleation sites, leading to a reduction in active centers and a lower monomer conversion rate. Higher emulsifier dosage affects initiator decomposition and free radical diffusion, further decreasing monomer conversion. The gelation rate initially decreases and then increases with increasing emulsifier dosage. With less emulsifier, uneven charge distribution or insufficient steric hindrance on the latex particle surface leads to insufficient electrostatic repulsion between particles, making them prone to collisions and resulting in aggregation and gel formation. With more emulsifier, excessive emulsifier affects the polymerization process, such as the initiator decomposition rate and free radical diffusion, indirectly leading to increased gelation. The emulsion particle size decreases with increasing emulsifier dosage. Increased emulsifier dosage creates a more stable emulsifier adsorption layer on the monomer surface, allowing droplets to exist stably in the aqueous phase, thus increasing the number of particles and reducing their size. Considering factors such as monomer conversion rate, gelation rate, stability, and particle size, the amount of emulsifier was finally determined to be 2.2% to 2.4% of the mass of the acrylate emulsion raw material, with 2.3% being preferred.

[0023] In emulsion polymerization, introducing a small amount of adhesive functional monomers into the emulsion polymerization system can significantly improve the wet adhesion of the adhesive film to synthetic fibers and cotton fabrics, and improve the interfacial integrity after freeze-thaw cycles. Sodium alkyl succinate disulfonate contains disulfonic acid groups, which can form a dense charged layer on the surface of latex particles, improving the electrostatic-steric synergistic effect between pigments / fillers and fibers. The alkyl long chain has good compatibility with the acrylate backbone, anchoring to the adhesive film network after copolymerization, providing durable wet adhesion. When the dosage is below 0.14%, the crosslinking points are insufficient, and the improvement in wet peel strength is not significant; when it is above 0.16%, the emulsion viscosity increases sharply, easily forming flocculation and reducing storage stability. Considering the three indicators of adhesion, storage stability, and gelation rate, the final determined dosage of the adhesive is 0.14%~0.16% of the mass of the acrylate emulsion raw material, preferably 0.15%.

[0024] Emulsion polymerization initiators are substances that generate free radicals during emulsion polymerization, thereby initiating the reaction of the monomers. They are mainly classified into several categories: peroxide initiators, azo initiators, and redox initiators. The amount and type of initiator directly affect the reaction rate. Normally, the more initiator used, the more free radicals are generated, and the faster the polymerization rate. We can also adjust the molecular weight and molecular distribution of the polymer using initiators. More initiator results in more free radicals and a relatively higher rate of reaction termination. Lower molecular weights have narrower distributions, and fewer initiators generate fewer free radicals; higher molecular weights have wider distributions. Therefore, the appropriate amount of initiator is crucial for the reaction. This invention found that when the amount of ammonium persulfate initiator is 0.28% of the mass of the acrylate emulsion raw material, the emulsion separates after 72 hours. This is because the amount of initiator is too small, resulting in insufficient free radical generation, less polymer formation, and an inability to form a sufficient network structure to maintain the stability of the emulsion. The monomer conversion rate of the emulsion initially increases and then decreases with increasing initiator dosage. At lower initiator dosages, the production of free radicals is low, the reaction rate is slow, and the monomer conversion rate is low. At higher initiator dosages, the free radical concentration is high, making the reaction more prone to termination and reducing the reaction rate to some extent. Excessively high initiator dosages can also cause explosive polymerization, leading to a decrease in monomer conversion rate. The gelation rate of the emulsion increases with increasing initiator dosage. At lower initiator dosages, fewer cross-linking points are formed, the reaction is incomplete, and the gelation rate is low. At higher initiator dosages, more free radicals are produced, making particle aggregation more likely, thus increasing the gelation rate. Considering factors such as monomer conversion rate, gelation rate, stability, and particle size, the initiator dosage was ultimately determined to be 0.37%~0.39% of the mass of the acrylate emulsion raw material, preferably 0.38%.

[0025] This invention has found that using epoxy resin E51, compared to other epoxy resins such as E12, E20, and E44, can give acrylate emulsions better high-temperature resistance.

[0026] This invention has found that using vinyl silicone oil, compared to other organosilicones such as vinyltrimethoxysilane (A-151), vinyltriethoxysilane (A-171), and vinyltri(methoxyethoxy)silane (A-172), can give acrylate emulsions better high-temperature resistance.

[0027] In some preferred embodiments, in the method for preparing the high and low temperature resistant acrylate emulsion described in the first aspect, in step (2), the pre-emulsion accounts for 2% of the total pre-emulsion.

[0028] In some preferred embodiments, in the method for preparing the high and low temperature resistant acrylate emulsion described in the first aspect, in step (2), the portion of the ammonium persulfate aqueous solution accounts for 70% of the total ammonium persulfate aqueous solution.

[0029] In some preferred embodiments, in the method for preparing the high and low temperature resistant acrylate emulsion described in the first aspect, in step (2), the remaining pre-emulsion is added dropwise for a total of 3 hours.

[0030] In some preferred embodiments, in the method for preparing the high and low temperature resistant acrylate emulsion described in the first aspect, in step (2), the pH is adjusted to 7.5~8.5 with ammonia.

[0031] Secondly, the present invention provides an acrylate emulsion resistant to high and low temperatures prepared by the preparation method described in the first aspect.

[0032] Thirdly, the present invention provides the application of the high and low temperature resistant acrylic emulsion described in the second aspect as a high-temperature and low-temperature resistant film-forming agent in fabric coating finishing agents. Furthermore, the coating exhibits no adhesion at 50°C and no brittleness at -30°C.

[0033] Compared with the prior art, the beneficial effects of this invention are as follows: Before the addition of epoxy resin E51 and vinyl silicone oil for modification, the latex film formed by the acrylic emulsion becomes sticky at 30°C. After adding vinyl silicone oil and epoxy resin E51 to modify the acrylic emulsion, the latex film can remain non-sticky at 50°C and non-brittle at -30°C.

[0034] This invention successfully synthesized an acrylic emulsion that is non-sticky at 50°C and non-brittle at -30°C. The emulsion has a uniform particle size distribution and passed all stability tests, meeting the expected modification standards and satisfying the market requirements for coating finishing agents to withstand high and low temperatures. Attached Figure Description

[0035] Figure 1 Particle size distribution of epoxy resin E51 modified acrylate emulsions with different contents.

[0036] Figure 2 Infrared spectra of acrylate emulsion (a), epoxy-acrylate emulsion (b), and silicone epoxy-acrylate emulsion (c). Detailed Implementation

[0037] The present invention will be further described below with reference to the accompanying drawings and specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Operating methods not specifically specified in the following embodiments are generally performed under conventional conditions or as recommended by the manufacturer.

[0038] In the specific embodiment, the basic raw material composition of the acrylate emulsion is as follows: butyl acrylate, styrene, acrylic acid, acrylonitrile, isooctyl acrylate, epoxy resin E51, vinyl silicone oil, sodium bicarbonate, emulsifier 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate and ammonium persulfate, and the balance water; wherein the epoxy resin accounts for 5% of the raw material composition by mass, the vinyl silicone oil accounts for 2% of the raw material composition by mass, the sodium bicarbonate accounts for 0.5% of the raw material composition by mass, the emulsifier accounts for 2.3% of the raw material composition by mass, the adhesive accounts for 0.15% of the raw material composition by mass, and the ammonium persulfate accounts for 0.38% of the raw material composition by mass.

[0039] The basic preparation method of the acrylate emulsion used in the specific implementation includes the following steps: 1) First, accurately weigh the reaction monomers (BA, ST, AA, AN, 2-EHA) using an analytical balance, mix them evenly, and let them stand for later use. Add epoxy resin E51, vinyl silicone oil, water, sodium bicarbonate, and emulsifier 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate to a four-necked flask. After mechanically stirring evenly, add the mixed monomers and mechanically stir for 30 minutes at a speed of 500~600 rpm to prepare a pre-emulsion. Then, take it out for later use.

[0040] 2) Take 2% of the pre-emulsion, mix it with deionized water and the adhesive sodium alkyl succinate disulfonate, and transfer it to a four-necked flask. Set the rotation speed to 275 rpm, heat it in an experimental constant temperature water bath, and use N2 to purge to maintain an inert gas atmosphere. When the temperature reaches 80℃, add 70% APS aqueous solution and keep it warm for 15 minutes to obtain the seed emulsion. After the seed emulsion is prepared, slowly add the remaining pre-emulsion to the four-necked flask through a constant pressure dropping funnel (dropping time is 3h). After the drop is completed, keep it warm for 3h, then add the remaining 30% APS aqueous solution, continue to keep it warm for 1h, turn off the heating device, cool it to 40℃, adjust the pH to >7 with ammonia, cool it to room temperature, filter it through a 100-mesh filter and bottle it to obtain the acrylate emulsion.

[0041] In the specific implementation method, a polytetrafluoroethylene (PTFE) mold is used to make an acrylic emulsion into a latex film, and the performance of the latex film is then tested: First, an appropriate amount of emulsion is evenly coated onto the PTFE mold (1 mm). The coated PTFE mold is placed in an environment of 25°C and allowed to dry for one day. Then, the surface-dried latex film is placed in a high-temperature drying oven at 120°C for 10 minutes. After drying, the film is cooled down and the performance is tested.

[0042] High temperature resistance of latex film: The test was conducted in accordance with the textile industry standard FZ / T 01063-2008 "Determination of heat resistance and adhesion of coated fabrics". The dried film was folded in half and pressed with a 1kg weight. It was then placed in a designated constant temperature drying oven for 2 hours, removed, carefully separated, and then rated.

[0043] No adhesion (not sticky): When the samples are separated, there is no obvious adhesion; Slight adhesion (slightly sticky): When the samples are separated, there is slight adhesion; Adhesive (sticky): When the samples are separated, there is adhesion.

[0044] Low-temperature resistance test of latex film: The test is conducted in accordance with the textile industry standard FZ / T 01063-2008 "Determination method of heat resistance and adhesion of coated fabrics". The dried film is placed in a low-temperature refrigerator with constant and stable temperature for 24 hours. After that, it is taken out and folded in half to check whether there are creases, tears or other phenomena. If there are none, it is determined that the latex film can withstand this low temperature.

[0045] Emulsion storage stability test: The storage stability clause of the national standard GB / T 11175-2021 "Test Methods for Synthetic Resin Emulsions" was followed: Weigh 5 g ± 0.1 g of the emulsion into a 10 mL clean glass bottle, seal it, and place it in a high-temperature drying oven at (60 ± 2)℃ for 7 consecutive days. After cooling to room temperature, visually observe whether precipitation, stratification, clumping, or flocculation occurs.

[0046] The synthesis of acrylic emulsions involves the addition of both soft and hard monomers. Increased soft monomer content lowers the glass transition temperature (TVT), and vice versa. Current market demands require textile coating agents to operate between -30°C and -25°C under extreme conditions. To ensure the latex film remains non-brittle at -30°C, the TVT must be designed to be at least below -25°C. However, due to monomer reactions and cross-linking, the actual TVT may increase. This invention found that when the theoretical Tg of the acrylic emulsion is -30°C, the latex film is brittle at -30°C. When the theoretical Tg is -35°C or -40°C, the latex film remains soft at -30°C. To minimize the stickiness of the latex film at high temperatures, this invention specifically designs the theoretical TVT to -35°C by adjusting the monomer dosage and ratio. The actual Tg can be determined by DSC; the theoretical Tg is only for formulation design reference. The corresponding acrylate emulsion contains the following raw material composition: 34% butyl acrylate, 5% styrene, 1% acrylic acid, 9% acrylonitrile, and 6% isooctyl acrylate. Further research will be conducted using this monomer formulation.

[0047] This invention investigates the effect of epoxy resin E51 addition on acrylic emulsion. When the epoxy resin addition exceeds 10%, the emulsion stability deteriorates. Therefore, the E51 addition was investigated to be 0%-10% of the raw material composition mass. The preparation method was the same as the basic preparation method described above. The types and amounts of other raw materials were the same as the basic raw material composition described above. Only the water content was changed to make adaptive formulation adjustments. The research results are shown in Table 1 below.

[0048] Table 1 Table 1 shows that with increasing E51 content, the emulsion stability remained satisfactory, while the emulsion viscosity, monomer conversion rate, and gelation rate all increased slightly, mainly due to the increased crosslinking density caused by the addition of epoxy resin. With increasing E51 content, the low-temperature resistance to -30℃ remained satisfactory, while the high-temperature resistance initially improved and then deteriorated, with the best effect observed at 5% E51 content. Initially, the crosslinking density gradually increased, restricting molecular chain movement and making the material less prone to deformation and softening under heat. However, excessive addition resulted in an overly high crosslinking density, leading to excessively strong interaction between molecular chains, causing stress concentration within the material and thus reducing high-temperature resistance. (Table 1 and...) Figure 1 It can be seen that as the amount of E51 added increases, the emulsion particle size first decreases and then increases. When no E51 is added, the particle size is 106.3 nm. When the amount added reaches 7.5%, the particle size decreases to 34 nm. As the amount of E51 increases further, the particle size increases. Initially, as the amount of epoxy resin increases, the polar groups in the epoxy resin can be adsorbed on the surface of the emulsion particles, acting as emulsifiers. The increased emulsification makes it easier for monomers to form small droplets, thus reducing the particle size. When the amount of epoxy resin increases further, the viscosity of the system increases. High viscosity is not conducive to the diffusion of monomers and initiators, resulting in uneven polymerization reaction, thus increasing the particle size.

[0049] This invention investigates the effect of vinyl silicone oil addition on acrylic emulsions. When the amount of vinyl silicone oil added exceeds 3%, after the latex film is dried, there is obvious silicone oil enrichment and migration on the surface, which affects the appearance and adhesion of the coating. Therefore, the experiment explores that the amount of vinyl silicone oil added is 1%-3% of the raw material composition mass. The research results are shown in Table 2 below.

[0050] Table 2 Table 2 shows that the high-temperature stickiness gradually improves with increasing vinyl silicone oil content. However, when the content reaches 2.5% or higher, there is some silicone oil enrichment and migration on the dried film surface. Excessive addition affects the coating appearance and adhesion. Initially, as the content increases, the vinyl silicone oil molecular chains, due to their good flexibility, can insert into the acrylate polymer molecular chains. At high temperatures, this increases the distance between molecular chains, reduces the interaction forces between them, and lowers the glass transition temperature (Tg) of the polymer, making polymer chain movement easier and avoiding stickiness caused by difficulties in molecular chain movement. This also makes it less prone to brittleness at low temperatures. However, when the content is too high, the low surface tension of the vinyl silicone oil leads to a tendency for it to migrate to the surface during the film formation stage, resulting in silicone oil enrichment and migration on the film surface. Considering all factors, the recommended addition amount of vinyl silicone oil is 2%.

[0051] In addition, the study found that as the amount of vinyl silicone oil added increased, the particle size of the emulsion remained at around 60 nm with little change. Therefore, the amount of vinyl silicone oil added had little effect on the particle size of the emulsion.

[0052] This embodiment also provides a control acrylate emulsion, which is prepared according to the basic preparation method described above. The types and amounts of other raw materials are the same as those in the basic raw material composition described above. Only the water content is changed for adaptive formulation adjustment, without the addition of epoxy resin E51 and vinyl silicone oil. The research results are shown in Table 3 below.

[0053] Table 3 As shown in Table 3, the control acrylic emulsion exhibits severe adhesion at 30°C and brittleness at -30°C.

[0054] This invention achieves no adhesion at 50℃ and no cracking at -30℃ through synergistic modification of epoxy resin and vinyl silicone oil, which is significantly better than the control system and is inventive.

[0055] Figure 2 The infrared spectra of acrylate emulsion (a), epoxy-acrylate emulsion (b), and silicone epoxy-acrylate emulsion (c) are shown. Among them, silicone epoxy-acrylate emulsion (c) is obtained according to the above-mentioned basic raw material composition and basic preparation method; the only difference between epoxy-acrylate emulsion (b) and silicone epoxy-acrylate emulsion (c) is that the amount of vinyl silicone oil is 0 and water is used to make up the difference; the only difference between acrylate emulsion (a) and epoxy-acrylate emulsion (b) is that the amount of epoxy resin E51 is 0 and water is used to make up the difference.

[0056] like Figure 2 As shown in the infrared spectrum, 2950 cm⁻¹ -1The peaks on the left and right represent the symmetrical stretching vibrations of methyl (-CH3) and methylene (-CH2), respectively, at 1730 cm⁻¹. -1 It is the stretching vibration peak of the ester group (C=O), 1460 cm⁻¹ -1 The peak is the -CH2- bending vibration peak, at 1380 cm⁻¹. -1 It is a symmetrical deformation peak of -CH3, from a to b, 915 cm⁻¹ -1 The peak of the epoxy group in the epoxy resin disappears at 1640 cm⁻¹. -1 There are no peaks for double bond stretching vibrations on either side, 990 cm⁻¹ -1 The absence of obvious out-of-plane bending vibration peaks indicates that the epoxy resin reacted with the acrylic monomer, and that the epoxy resin was introduced into the system. From b to c, 1100 cm⁻¹ -1 The peak of the stretching vibration of Si-OC is located at 730 cm⁻¹. -1 765cm -1 825cm -1 The three absorption peaks are Si-C, and the final polymer contains absorption peaks of acrylates and organosilicon, indicating that vinyl silicone oil has been successfully introduced into the system.

[0057] Furthermore, it should be understood that after reading the above description of the present invention, those skilled in the art can make various alterations or modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims.

Claims

1. A method for preparing a high and low temperature resistant acrylic emulsion, characterized in that, The raw material composition of the high and low temperature resistant acrylic emulsion, by mass fraction, is as follows: 30%~35% butyl acrylate, 3%~6% styrene, 1%~2% acrylic acid, 5%~10% acrylonitrile, 5%~10% isooctyl acrylate, 4%~6% preferably 5% epoxy resin E51, 1.9%~2.1% preferably 2% vinyl silicone oil, 0.5%~1% sodium bicarbonate, 2.2%~2.4% preferably 2.3% emulsifier 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate, 0.14%~0.16% preferably 0.15% adhesive alkyl succinate disulfonate and 0.37%~0.39% preferably 0.38% ammonium persulfate, and the balance being water; The theoretical glass transition temperature of the high and low temperature resistant acrylic emulsion, calculated using the Fox equation, is -35 to -40°C. The preparation method employs a semi-continuous seed emulsion polymerization method, specifically including the following steps: (1) Epoxy resin E51, vinyl silicone oil, water, sodium bicarbonate and emulsifier 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate are mixed and then mixed monomers are added. The mixed monomers are butyl acrylate, styrene, acrylic acid, acrylonitrile and isooctyl acrylate. The mixture is stirred to form a pre-emulsion. (2) Take a portion of the pre-emulsion and mix it with water and the adhesive sodium alkyl succinate disulfonate. Heat it to 80-82°C in an inert atmosphere under stirring at 250-300 rpm, preferably 275 rpm. Then add a portion of ammonium persulfate aqueous solution and keep it warm for 15-20 minutes to obtain the seed emulsion. Then add the remaining pre-emulsion dropwise to the seed emulsion. After the addition is complete, keep it warm for 3-4 hours. Then add the remaining ammonium persulfate aqueous solution and continue to keep it warm for 1-1.5 hours. Cool down and adjust the pH to >7. Filter to obtain the high and low temperature resistant acrylate emulsion.

2. The preparation method according to claim 1, characterized in that, In step (2), the pre-emulsion accounts for 2% of the total pre-emulsion.

3. The preparation method according to claim 1, characterized in that, In step (2), the portion of the ammonium persulfate aqueous solution accounts for 70% of the total ammonium persulfate aqueous solution.

4. The preparation method according to claim 1, characterized in that, In step (2), the remaining pre-emulsion is added over a total of 3 hours.

5. The preparation method according to claim 1, characterized in that, In step (2), the pH is adjusted to 7.5-8.5 with ammonia.

6. The high and low temperature resistant acrylate emulsion prepared by the preparation method according to any one of claims 1 to 5.

7. The application of the high and low temperature resistant acrylic emulsion according to claim 6 as a high and low temperature resistant film-forming agent in fabric coating finishing agents.

8. The application according to claim 7, characterized in that, The coating does not stick at 50°C and does not crack at -30°C.